The Effect of Picture and Picture Integration with Guided Note Taking accompanied by Optimization of Teaching Aids Learning Outcomes - Annisa Nur Khasanah; Slamet Santosa; Meti Indrowati; Arifin Septiyanto (Postgraduate, University of Mataram, 2022)
The objective of this study is to determine the impact of the Picture and Picture application integrated with Guided Note Taking (GNT) on students' biology learning achievement by optimizing teaching aids. The study is categorized as a quasi-experiment. The research design used is Post-test Only Control Group Design with group experiment, which implements Picture and Picture application coupled with Guided Note Taking (GNT) through the optimization of the use of teaching aids, and control group, which implements discussion technique, speech, and presentation. The population of the research is students of class XI IPA (grade 11 in Natural Science) from Public Senior High School (SMA N) 2 Boyolali. The sample in the research is students of class XI IPA 4 as the experiment group and students of class XI IPA 3 as the control group. Cluster random sampling was used to collect the sample. Multiple-choice tests, questionnaires, observation forms, and documentation are used to collect data. The t-test was used to test the hypothesis. This study concludes that Picture and Picture application integrated with Guided Note Taking (GNT) through the optimization of teaching aids utilization affects students' biology learning achievement in cognitive, affective, and psychomotor domains.